Targeting DNA Repair through Podophyllotoxin and Rutin Formulation in Hematopoietic Radioprotection: An in Silico, in Vitro, and in Vivo Study - Yashavarddhan, M. H.; Shukla, Sandeep K.; Chaudhary, Pankaj; Srivastava, Nitya N.; Joshi, Jayadev; Suar, Mrutyunjay; Gupta, Manju L. (Frontiers in Pharmacology, 2017)
Drug discovery field has tremendously progressed during last few decades however an effective radiation countermeasure agent for the safe administration to the victims of radiation exposure is still unavailable. This multi-model study is aimed at elucidating the mechanistic aspects of a novel podophyllotoxoin and rutin combination (henceforth referred as G-003M) in the hematopoietic radioprotection and its involvement in the DNA damage and repair signalling pathways. Using in-silico study, we identified the binding sites and structural components of G-003M and validated in-vitro. We further studied various in-vivo endpoints related to the DNA repair and cell death pathways in mice pre-administered with G-003M, irradiated and subsequently euthanized to collect blood and bone marrow cells. In-silico study showed the binding of podophyllotoxin to β-tubulin and presence of a functional hydroxyl group in the rutin, suggested their involvement in G2/M arrest and the free radical scavenging respectively. This experimentation was further validated through in-vitro studies. In-vivo mice studies confirmed that G-003M pre-administration attenuated DNA damage and enhanced repair after whole body exposure. We further noticed a decrease in the levels of γH2AX, p53BP1, and ATM kinase and an increase in the levels of DNA pk, Ku80, Ligase IV, Mre 11, Rad 50 and NBS 1 in the blood and bone marrow cells of the G-003M pre-administered and irradiated mice. We noticed an overall increase in the pro-survival factors in the G-003M pre-treated and irradiated groups establishing the radioprotective efficacy of this formulation. The lead obtained from this study will certainly help in developing this formulation as a safe and effective radioprotector which could be used for humans against any planned or emergency exposure of radiation.